2018
DOI: 10.3390/en11071828
|View full text |Cite
|
Sign up to set email alerts
|

A Fast DC Fault Detection Method for Multi-Terminal AC/DC Hybrid Distribution Network Based on Voltage Change Rate of DC Current-Limiting Inductor

Abstract: The rapid detection of direct current (DC) faults is one of the key technologies for the development of multi-terminal alternating current (AC)/DC hybrid distribution networks. The DC fault current rises quickly and affects the whole network. Therefore, DC faults must be detected much faster than AC faults. This paper proposes a fast DC fault detection method based on the voltage change rate of the current-limiting inductor (CLI) for the multi-terminal AC/DC hybrid distribution network. Firstly, the characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…The DC reactor has also been proposed for use as a means for fast and accurate dc fault detection in a meshed multiterminal HVDC grid [112], [113]. The rate of change of the voltage across the DC reactor is compared with predefined protection voltage thresholds.…”
Section: B the Inductormentioning
confidence: 99%
“…The DC reactor has also been proposed for use as a means for fast and accurate dc fault detection in a meshed multiterminal HVDC grid [112], [113]. The rate of change of the voltage across the DC reactor is compared with predefined protection voltage thresholds.…”
Section: B the Inductormentioning
confidence: 99%
“…The DC reactors were connected at each end of the cable. In Reference [22], the voltage change rate of a DC current limiting inductor (CLI) has been proposed to detect a fault in a multiterminal AC/DC hybrid distribution network. The CLIs were implemented at each end of a cable.…”
Section: Di/dtmentioning
confidence: 99%
“…Currently, in the study of fault diagnosis in AC-DC hybrid grids, The literature [4] shows that the Industrial frequency quantity distance protection is not applicable to the AC-DC hybrid grid, so a new criterion is proposed to determine the faults inside and outside the zone by solving the time-domain equations, and it is found that the fault characteristics of the hybrid grid are almost the same in the frequency domain under the faults with different transition resistances, so the criterion is not affected by the transition resistances. In the literature [5], for DC line faults in hybrid AC-DC distribution networks, a threshold value is set for the rate of voltage change of the single-end current-limiting inductor of the DC line to detect the occurring faults, and this criterion can effectively detect the three fault cases of bipolar DC lines. Related research shows that fault diagnosis by setting thresholds can effectively achieve fault diagnosis of in-and out-of-area faults, but when there are too many grid lines it is impossible to determine the fault line, and there are limitations that make it difficult to be applied in fault diagnosis of large AC-DC hybrid grids.…”
Section: Introductionmentioning
confidence: 99%